Taxifolin: A Potential Therapeutic Agent for Cerebral Amyloid Angiopathy - Saito, Satoshi; Tanaka, Masashi; Satoh-Asahara, Noriko; Carare, Roxana Octavia; Ihara, Masafumi (Frontiers in Pharmacology, 2021)
Cerebral amyloid angiopathy (CAA) is characterized by the accumulation of β-amyloid (Aβ) in the walls of cerebral vessels, leading to complications such as intracerebral hemorrhage, convexity subarachnoid hemorrhage and cerebral microinfarcts. Patients with CAA-related intracerebral hemorrhage are more likely to develop dementia and strokes. Several pathological investigations have demonstrated that more than 90% of Alzheimer’s disease patients have concomitant CAA, suggesting common pathogenic mechanisms. Potential causes of CAA include impaired Aβ clearance from the brain through the intramural periarterial drainage (IPAD) system. Conversely, CAA causes restriction of IPAD, limiting clearance. Early intervention in CAA could thus prevent Alzheimer’s disease progression. Growing evidence has suggested Taxifolin (dihydroquercetin) could be used as an effective therapy for CAA. Taxifolin is a plant flavonoid, widely available as a health supplement product, which has been demonstrated to exhibit anti-oxidative and anti-inflammatory effects, and provide protection against advanced glycation end products and mitochondrial damage. It has also been shown to facilitate disassembly, prevent oligomer formation and increase clearance of Aβ in a mouse model of CAA. Disturbed cerebrovascular reactivity and spatial reference memory impairment in CAA are completely prevented by Taxifolin treatment. These results highlight the need for clinical trials on the efficacy and safety of Taxifolin in patients with CAA.